(untitled) (Journal of actual problems of jurisprudence, 2019)
Thus, the investigator, assessing the evidence collected in the case on its internal belief, guided by the law and conscience, concludes that actual and legal grounds for termination of the criminal case. This result it is a logical conclusion drawn from the analysis of objective reality, established by sufficient set of reliable evidence. Giving this procedural the negative colouring and elevation to the rank of minor act, and often marriage the work of the investigator, I think, is unacceptable.